THE INFLUENCE OF PRODUCT REVIEW AND CONSUMER TRUST ON CONSUMER PURCHASE INTENTION OF ELECTRIC VEHICLE IN MANADO - Liusito, Jenifer R. K.; Pandowo, Merinda H. C.; Tielung, Maria V. J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2024)
With the rapid development of technology in the automotive field, electric vehicles can be an alternative solution to solve environmental problems. The Indonesian government has promoted and supported the transition to electric vehicles by implementing various policies and incentives aimed at reducing environmental impact and fostering a greener transportation system. The purpose of this study is to ascertain the influence of product review and consumer trust on consumer purchase intention of electric vehicle in Manado. This study uses a quantitative with causal research approach. The data collected through questionnaire with convenience sampling technique that observed 100 respondents who have an intention to purchase electric vehicle and analyzed using Multiple Linear Regression Analysis. The findings of this study have shown that product review and consumer trust have a significant positively effect on consumer purchase intention of electric vehicle, both partially and simultaneously. This study can provide a reference for producers and marketers to improve their marketing strategies to gain valuable feedback through product review and consumer trust in increasing consumer purchase intention.   Keywords: Product Review, Consumer Trust, Consumer Purchase Intention